Very high interest rates and the cousin risks: Brazil during the Real Plan - Márcio Gomes Pinto Garcia; Tatiana Didier (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2000)
We review the arguments in the finance and open macroeconomics literature relevant for the Central Bank to set the level of the interest rate in an open economy. The two relevant risks are the currency and country risks. The country risk (Brazil Risk) is measured with different financials instruments and the (unobservable) currency risk is estimated via the Kalman Filter. We show that besides the currency risk, which is also relevant in developed economies the country risk is of utmost importance to determine the domestic interest rates. Both risks share a few common causes, which is why we call them the cousin risks. Thus, when and if those common causes are confronted, the fall of domestic interest rates may be substantial, because both currency and Brazil risks will fall simultaneously. Preliminary results identify some components of the Brazil risk, e.g., the fiscal deficits, and the domestic and international financial markets conditions. The convertibility risk, defined as risk associated with possibility of not being able to convert BRLs into foreign currency, showed up as an important cause of the Brazil risk during the international financial crises periods, but is no longer relevant. Nowadays, Brazil risk decreased significantly, but the same did not happen with the currency risk. Therefore, it seems that the main factor precluding the fall in domestic interest rates may be associated with the uncertainty of the future behavior of the balance payments, especially the trade account. In view of this hypothesis, we might speculate that assuring vigorous export growth, without resorting to devaluation, is fundamental to achieve lower real interest rates, compatible with sustained economic growth.
Keywords: C29; F31; G15; 330